Pengaruh Budaya Organisasi dan Kemampuan Kerja Terhadap Kinerja Personel Satuan Reserse dan Kriminalitas (RESKRIM) Polres Sumenep dengan Reward Sebagai Variabel Mediasi - Ifan Prayitno; Mei Indrawati; Chamariyah Chamariyah (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
Abstract The research results show that: 1) Organizational culture has a direct and significant positive effect on personnel performance as evidenced by the original sample value of 0.251 and p-values ​​of 0.023. 2) Organizational culture has no direct positive or significant effect on performance as evidenced by the original sample value of 0.149 and p-values ​​of 0.432. 3) Work ability has a direct and significant positive effect on personnel performance as evidenced by the original sample value of 0.347 and p-values ​​of 0.021. 4) Work ability has a direct and significant positive effect on rewards as evidenced by the original sample value of 0.669 and p-values ​​of 0.000. 5) Rewards have a direct and significant positive effect on personnel performance as evidenced by the original sample value of 0.475 and p-values ​​of 0.000. 6) Organizational culture has no positive but significant indirect effect on personnel performance and rewards as evidenced by the original sample value of 0.071 and p-values ​​of 0.480. 7) Work ability has a significant positive indirect effect on personnel performance and rewards with a path coefficient value of 0.317 and a p-value of 0.000.